Identification of specialized pro-resolving mediator clusters from healthy adults after intravenous low-dose endotoxin and omega-3 supplementation: a methodological validation. Issue 1 (December 2018) - Norris, Paul; Skulas-Ray, Ann; Riley, Ian; Richter, Chesney; Kris-Etherton, Penny; Jensen, Gordon; Serhan, Charles; Maddipati, Krishna
Abstract Specialized pro-resolving mediator(s) (SPMs) are produced from the endogenous ω-3 polyunsaturated fatty acids (PUFA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and accelerate resolution of acute inflammation. We identified specific clusters of SPM in human plasma and serum using LC-MS/MS based lipid mediator (LM) metabololipidomics in two separate laboratories for inter-laboratory validation. The human plasma cluster consisted of resolvin (Rv)E1, RvD1, lipoxin (LX)B4, 18-HEPE, and 17-HDHA, and the human serum cluster consisted of RvE1, RvD1, AT-LXA4, 18-HEPE, and 17-HDHA. Human plasma and serum SPM clusters were increased after ω-3 supplementation (triglyceride dietary supplements or prescription ethyl esters) and low dose intravenous lipopolysaccharide (LPS) challenge. These results were corroborated by parallel determinations with the same coded samples in a second, separate laboratory using essentially identical metabololipidomic operational parameters. In these healthy subjects, two ω-3 supplementation protocols (Study A and Study B) temporally increased the SPM cluster throughout the endotoxin-challenge time course. Study A and Study B were randomized and Study B also had a crossover design with placebo and endotoxin challenge. Endotoxin challenge temporally regulated lipid mediator production in human serum, where pro-inflammatory eicosanoid (prostaglandins and thromboxane) concentrations peaked by 8 hours post-endotoxin and SPMs such as resolvins and lipoxins initially decreased by 2 h and were then elevated at 24 hours. In healthy adults given ω-3 supplementation, the plasma concentration of the SPM cluster (RvE1, RvD1, LXB4, 18-HEPE, and 17-HDHA) peaked at two hours post endotoxin challenge. These results from two separate laboratories with the same samples provide evidence for temporal production of specific pro-resolving mediators with ω-3 supplementation that together support the role of SPMin vivo in inflammation-resolution in humans.